Politics, Markets and EU Gas Supply Security: Case Studies of the UK and Germany - Kopp, Sandu-Daniel (Springer, 2015)
Sandu-Daniel Kopp investigates whether carbon reduction targets are compatible with market-driven competition in gas (and power) industries, and whether security of supply is compatible with competitive markets. He examines the policy trade-offs which need to be made between the three different elements, and whether these policy judgements should be economically or politically based. The analysis shows the need for a complex set of politically determined options to protect (competitive) markets from price risks and emergency events and demonstrates that this has thus far failed the policy test. Overall, the author argues that the three major elements of EU energy policy are incompatible in important respects and thereby challenges much of the conventional wisdom of EU and Member State policies of the past decade.